Respuesta :

Answer:

A). 2x^2(2x^2 + 5x + 1)

B). (x + 6)(x + 7)

Step-by-step explanation:

A). 4x^4+10x^3+2^2

I assume the problem is

4x^4 + 10x^3 + 2x^2

Look at he number parts, 4, 10, 2. They have a common factor of 2.

Now look at the variable parts, x^4, x^3, x^2. They have a common factor of x^2.

We factor out 2x^2 from every term.

4x^4 + 10x^3 + 2x^2 =

= 2x^2(2x^2 + 5x + 1)

B). x^2 + 13x + 42

We need to find two numbers whos product is 42 and whose sum is 13. The numbers are 6 and 7.

x^2 + 13x + 42 =

= (x + 6)(x + 7)